Digital Marketing for Startup: A Systematic Literature Review - Ni Putu Nurwita Pratami Wijaya; Vanessa Gaffar; Bambang Widjajanta; Denny Andriana; Dwinto Martri Aji Buana; Rennyta Yusiana (Journal of Islamic Economics and Business, 2025)
Startups encounter obstacles including constrained resources, minimal brand recognition, and fierce competition. Digital marketing provides economical solutions; nevertheless, its strategic application in startup environments is still little examined. This study intends to examine digital marketing methods appropriate for startups using a thorough literature review. This research innovatively synthesizes fragmented knowledge to determine the best efficient digital marketing strategies for early-stage enterprises. The overall population for this study comprised 1,709 articles, with a sample size of 50 articles. The study's findings indicate that start-ups face multiple challenges, one of which is securing capital. Consequently, start-ups must implement a suitable approach, wherein digital marketing is employed to address their challenges. The findings of this research indicate that digital marketing is crucial for the survival and success of startups in competitive business environments.